Genome-wide microsatellite characterization and their marker development and transferability in Broussonetia Species - Xiaowen Jia; Hanyu Li; Ying Han; Lu Wang; Chanjuan Lai; Xi Liu; Pan Li; Zupei Lei; Yonghua Zhang (BMC Genomics)
Abstract Background Broussonetia papyrifera, B. monoica, and B. kaempferi belong to the genus Broussonetia (Moraceae). These three species hold significant economic and research values. However, few molecular markers have been effectively utilized for resource development and molecular genetic breeding of these species. Sequencing of their genomes allowed us to develop genomic markers (e.g. simple sequence repeats (SSRs)) and construct a high-density physical map. Results A total of 369,557, 332,627, and 276,245 SSRs were identified in 13 high-quality assembled pseudochromosomes and their unassembled scaffolds for B. papyrifera, B. monoica, and B. kaempferi, respectively. Among the identified genomic SSRs across the three species, short repeat sequences were more abundant, while long repeat sequences constituted a smaller proportion. Additionally, the predominant repeat motifs in the SSRs of the three Broussonetia species were composed of ‘A’ and ‘T’ repeats. Using B. papyrifera genome as a reference, 4,419 common SSRs were identified among these three species, while 2,048 SSRs were specific to B. kaempferi, and 4,285 SSRs were specific to B. monoica. Distribution analysis indicated a notable similarity in the distribution patterns of SSRs across the pseudochromosomes of these three species. Furthermore, of the identified SSRs, 28%, 31%, and 24% were mapped to genes in B. papyrifera, B. kaempferi, and B. monoica, respectively. Genic-mapped SSRs may regulate biological processes by influencing gene activity and protein function. To verify SSRs polymorphism, we selected 30 ones from 10,752 potentially polymorphic SSRs loci for PCR amplification among these three species, all of which were successfully amplified and exhibited polymorphism across these three species. Conclusions These findings are helpful for further research on the origin, evolution, and migration of Broussonetia species and also laid the foundation for the precise identification, systematic evaluation, and efficient utilization of the germplasm resources of Broussonetia species.